2010
DOI: 10.1097/nnr.0b013e3181dbb2e2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Implementation Fidelity in a Community-Based Parenting Intervention

Abstract: Background Establishing the feasibility and validity of implementation fidelity monitoring strategies is an important methodological step in implementing evidence-based interventions on a large scale. Objectives The objective of the study was to examine the reliability and validity of the Fidelity Checklist, a measure designed to assess group leader adherence and competence delivering a parent training intervention (the Chicago Parent Program) in child care centers serving low-income families. Method The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 28 publications
(41 reference statements)
3
119
1
2
Order By: Relevance
“…Though a few recent studies have developed fidelity assessment tools based on a self-reported measure of behavioral health provider fidelity [45] or expert ratings for delivering a complex intervention for chronic pain [46] and a practice change intervention [47] (both of the latter instruments assessed face validity and reliability only), the dearth of validated and published instruments extends beyond weight loss interventions and is well-recognized [48,49,9,[50][51][52][53]. Clearly, there is a need for validated measures to help determine the effectiveness of weight loss interventions when delivered as they were intended.…”
Section: Original Research Discussionmentioning
confidence: 99%
“…Though a few recent studies have developed fidelity assessment tools based on a self-reported measure of behavioral health provider fidelity [45] or expert ratings for delivering a complex intervention for chronic pain [46] and a practice change intervention [47] (both of the latter instruments assessed face validity and reliability only), the dearth of validated and published instruments extends beyond weight loss interventions and is well-recognized [48,49,9,[50][51][52][53]. Clearly, there is a need for validated measures to help determine the effectiveness of weight loss interventions when delivered as they were intended.…”
Section: Original Research Discussionmentioning
confidence: 99%
“…For Hispanic families, unique risk factors associated with immigration (e.g., adapting to a new culture, language barriers) may compromise family functioning, an important buffer against negative adolescent behavioral outcomes [20]. Characteristics of the family may also impact intervention attendance, which has been positively associated with ratings of fidelity [21]. In previous Familias Unidas efficacy trials, family characteristics (e.g., stress, income, and adolescent behavior problems) were significantly associated with initial engagement to the intervention [22].…”
Section: Participant Variablesmentioning
confidence: 99%
“…Adjustments, informed by the way the Fidelity Checklist items overlapped with FIOC curricular content and intent, were made by the first author working with a doctoral student who later served as one of the QAAs (see Table 1 for a summary of the adjusted items and mean competence scores). As an example of item adjustment, Breitenstein et al (2010) worked with a group of parents and created the study instrument for these sessions. In contrast, in the current study, only one family participated in the sessions, so the original Fidelity Checklist item ''actively engages all parents in the discussion'' was reworded as ''actively engages both parents in the discussions and activities.''…”
Section: Methodsmentioning
confidence: 99%
“…ICCs were .79 and .55 for the adherence and competence scores, respectively. Internal consistency for the competence scale was high (Cronbach's alpha = .96), and the high intercorrelation between the competence scale item sets adapted from the Breitenstein et al Content/process ratings of ''figuring it out for the child'' sessions To evaluate the emotional tenor of each session, QAAs rated parents' level of conflict (from 0 = no conflict to 4 = very high conflict) and overall tone of the session (quality and affective tone of conversations) on a 9-point scale (1Y3 = negative, 4Y6 = neutral, 7Y9 = positive) on the Fidelity Checklist (Breitenstein et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation